Rutin and Melatonin ameliorate the gastrointestinal and hepatic injuries induced by oral Lead Acetate in rats (2023)
Background: Oral ingestion of lead in drinking water represents the most common route of human and animal exposure, especially in the developing nations. Unlike other internal organs, research on the effects of lead on gastrointestinal tract remains limited. This study explored the alterations in faecal fatty acid composition, gastrointestinal and hepatic histologies and redox status, following chronic, 90-day exposure of rats to lead acetate (PbA). We also investigated the protective effects of rutin and melatonin against lead toxicity in rats. Methods: Fifty male Wistar rats were randomly divided into five groups of 10 (A-E) and were assigned as follows: A: Control; B: 1% PbA in drinking water; C: PbA+rutin (50 mg/kg); D: PbA+melatonin (25 mg/kg) and E: PbA+rutin+melatonin. The faecal fatty acid profiles were quantified by methylation and gas chromatography-flame ion detection. We also evaluated the oxidative stress and antioxidant markers for the stomach, liver, and guts, and their histopathological alterations. Results: Exposure to PbA caused remarkable elevations of the faecal fats, such as undecylic, lauric, tridecylic, myristic, and palmitic acids, compared to the controls and rats in group C. The administration of rutin and/or melatonin ameliorated the PbA-induced increases in the hydrogen peroxide and malondialdehyde contents. Rutin and melatonin improved the levels of thiol, and reduced the glutathione, glutathione S-transferase and superoxide dismutase activities. Conclusion: The findings suggest that rutin alone or combined with melatonin protects against PbA-induced disruption of the liver and gastrointestinal tract integrity via modulation of intestinal total lipids in cells and redox imbalances.